Apply Membrane Biological Reactor (MBR) in Industrial wastewater treatment: A Mini Review - Samar S. Al-Khafaji; Wisam S. Al-Rekabi; Mohammed J. mawat (Genius Journals, 2022)
As an economical option to create nutrient-rich, solids-free effluents with a significant level for pathogen removal, while taking up little space compared to other treatment units, membrane bioreactor technology for municipal and industrial wastewater treatment is rapidly being investigated in recent years. Numerous research has used a variety of reactor designs in conjunction with membranes in the past, particularly in the previous ten years. With an emphasis on several types of membrane-coupled reactors, such as submerged and external membrane types, this paper critically assesses the potential of membrane bioreactor technology for the treatment of industrial wastewater. Additionally, this review paper addresses the effects of numerous parameters, including benefits and drawbacks, on the biological and filtration performances of membrane bioreactors for two types external membrane and submerged membrane
Keywords: membrane; biological; filtration; bioreactors